Biological impact of an enhanced recovery after surgery programme in liver surgery. Issue 2 (22nd December 2020) - Gonvers, S; Jurt, J; Joliat, G -R; Halkic, N; Melloul, E; Hübner, M; Demartines, N; Labgaa, I
Abstract: Background: The clinical and economic impacts of enhanced recovery after surgery (ERAS) programmes have been demonstrated extensively. Whether ERAS protocols also have a biological effect remains unclear. This study aimed to investigate the biological impact of an ERAS programme in patients undergoing liver surgery. Methods: A retrospective analysis of patients undergoing liver surgery (2010–2018) was undertaken. Patients operated before and after ERAS implementation in 2013 were compared. Surrogate markers of surgical stress were monitored: white blood cell count (WBC), C-reactive protein (CRP) level, albumin concentration, and haematocrit. Their perioperative fluctuations were defined as Δvalues, calculated on postoperative day (POD) 0 for Δalbumin and Δhaematocrit and POD 2 for ΔWBC and ΔCRP. Results: A total of 541 patients were included, with 223 and 318 patients in non-ERAS and ERAS groups respectively. Groups were comparable, except for higher rates of laparoscopy (24.8 versus 11.2 per cent; P < 0.001) and major resection (47.5 versus 38.1 per cent; P = 0.035) in the ERAS group. Patients in the ERAS group showed attenuated ΔWBC (2.00 versus 2.75 g/l; P = 0.013), ΔCRP (60 versus 101 mg/l; P <0.001) and Δalbumin (12 versus 16 g/l; P < 0.001) compared with those in the no-ERAS group. Subgroup analysis of open resection showed similar results. Multivariable analysis identified ERAS as the only independent factor associated with high ΔWBC (odds ratio (OR) 0.65, 95 per cent c.i. 0.43 to 0.98; P = 0.038), ΔCRP (OR 0.41, 0.23 to 0.73; P = 0.003) and Δalbumin (OR 0.40, 95 per cent c.i. 0.22 to 0.72; P = 0.002). Conclusion: Compared with conventional management, implementation of ERAS was associated with an attenuated stress response in patients undergoing liver surgery.